Study on the Effects of Ginger Extract on the Degree of Hydrolysis, Sensory Evaluation, Color Difference, and Volatile Flavor Components of Oyster Enzymatic Hydrolysate - Lin, Yijun; Pan, Fengqiong; Chen, Xueren; Chen, Xueren; Huang, Jiating; Lu, Yuhua; Yang, Zhao (Transactions on Environment, Energy and Earth Sciences, 2024)
To investigate the impact of ginger extract on the quality of oyster enzymatic hydrolysate (OEH), the effects of adding 4% and 8% ginger juice on hydrolysis degree, sensory evaluation, color difference, and volatile flavor components were analyzed. The results indicated that the highest hydrolysis degree of OEH, achieved by adding 8% ginger juice, was 25.27%, and the highest sensory score reached 85.6. Furthermore, 24 and 36 compounds were identified in OEH with 4% and 8% ginger juice added, respectively.